PENGARUH EDUKASI BERBASIS YOUTUBE TERHADAP PENGETAHUAN DAN SIKAP TENTANG CYBERSEX DI SMP NEGERI 1 KEDUNGPRING - Kasta, Malika Alya Kasta; Ekawati, Heny; Gumelar, Wahyu Retno (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2025)
Objective: Cybersex is a deviant sexual behavior that can threaten adolescent development if not accompanied by appropriate understanding and attitudes. Health education through digital media, such as YouTube, is an effective alternative in the modern era. This study aims to determine the effect of YouTube video-based education on adolescents' knowledge and attitudes about cybersex at SMP Negeri 1 Kedungpring, Lamongan. Methods: The method used was quantitative, with a pre-experimental pretest-posttest design on 283 eighth-grade students using a total sampling method. Data were collected using a closed-ended questionnaire and analyzed using the Wilcoxon test using SPSS. Results: The results showed that before education, 54.8% of students had high knowledge, increasing to 66.4%, and 84.1% had moderate attitudes. After education, the moderate attitude level increased to 90.8%. The results showed a significant difference (p = 0.000 for knowledge and p = 0.000 for attitudes) in both variables, indicating a significant influence between adolescents' knowledge and attitudes before and after YouTube video-based education. Conclusion: It is concluded that YouTube video-based education is an alternative that can improve the knowledge and attitudes of teenagers because audiovisual media such as YouTube videos can present information in a more interesting, clear, and easy-to-understand way.